IMPLEMENTASI METODE SMART DALAM SISTEM PENUNJANG KEPUTUSAN UNTUK OPTIMALISASI PEMILIHAN PEMASOK DAGING (STUDI KASUS: BERKAT AGRO MANDIRI) - Sakti Alfindo Bihalalika; Iis Aisyah (Journal of Research and Publication Innovation, 2025)
In the context of globalization which accelerates the pace of competition between business actors, supplier selection is a crucial element in ensuring product quality and supply chain stability. This research focuses on the development of a decision support system with an approach based on the Simple Multi-Attribute Rating Technique (SMART) method to optimize meat supplier selection for Berkat Agro Mandiri. Data were collected through literature reviews, interviews, and observations, then processed using the SMART method to produce objective evaluations.The SMART calculation results show that the highest-scoring supplier is Victory Beef Supplier, with a final score of 0.96667, followed by other suppliers with lower scores. Rankings are based on criteria such as price, tax, product quality, service, and location, which were normalized and analyzed to deliver objective decisions. Keywords: SMART method, supplier selection, decision support system, operational efficiency, berkat agro mandiri;